2014
DOI: 10.1108/jmp-02-2012-0040
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between status judgments, identification, and counterproductive behavior

Abstract: Purpose – The purpose of this paper is to investigate the relationships among perceived external prestige (PEP), perceived internal respect (PIR), organizational and work-group identification (OID and WID), and counterproductive work behavior (CWB). Design/methodology/approach – Data were gathered from a cement firm's employees, using longitudinal research. Descriptive statistics, confirmatory factor analysis and structural equation mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 59 publications
2
33
0
2
Order By: Relevance
“…In addition, organizations need to be alert to changes in employees' sense of identity, since our study showed that employees' disapproval will be more reflected in the CWB-O. This result extended the negative influence from OI to CWB in a more nuanced way (e.g., [30,90]). To maintain the belongingness and loyalty of employees, the company must avoid unethical and dishonest behaviors like corporate hypocrisy.…”
Section: Practical Implicationssupporting
confidence: 64%
“…In addition, organizations need to be alert to changes in employees' sense of identity, since our study showed that employees' disapproval will be more reflected in the CWB-O. This result extended the negative influence from OI to CWB in a more nuanced way (e.g., [30,90]). To maintain the belongingness and loyalty of employees, the company must avoid unethical and dishonest behaviors like corporate hypocrisy.…”
Section: Practical Implicationssupporting
confidence: 64%
“…The surrounding context may also affect whether a supervisor's high SDO manifests in abusive behavior. We propose that two kinds of threats, namely positional instability and perceived low internal respect (Ali Al-Atwi & Bakir, 2014;Williams, 2014), could exacerbate abusive behavior by supervisors with high SDO. Such threats may motivate them to abuse subordinates as a means of protecting their power.…”
Section: Introductionmentioning
confidence: 98%
“…Este logro, aunque parcial, corrobora el supuesto básico del enfoque del envejecimiento exitoso en el trabajo, al mostrar que algunas estrategias SOC afectan al impacto que el ambiente de trabajo negativo (ITM) puede tener sobre el absentismo de los trabajadores mayores de 55 años. Hasta el presente se había desarrollado un importante cuerpo de investigación empírica que avalaba el impacto positivo de la identificación social en el trabajo -grupal, organizacional, profesional-sobre las actitudes y conductas de los integrantes de la organización (Ali Al-Atwi y Bakir, 2014;Cheung y Wu, 2014;Elliott, et al, 2015). Sin embargo, este estudio va un paso más allá, explorando las consecuencias negativas de la identificación con una categoría desvalorizada socialmente, como son los mayores.…”
Section: Discussionunclassified